Primary Treatment of Domestic Wastewater with the Use of Unmodified and Chemically Modified Drinking Water Treatment Sludge (2022)
ABSTRACT: Improved wastewater (WW) treatment contributes to preserving human life and aquatic ecosystems and acting on climate change. The use of drinking water treatment sludges (WTS) as coagulants in the primary treatment of WW contributes, in this regard, and simultaneously enables the sustainable management of this waste. In this work, the improvement of the primary treatment of real domestic WW using unmodified WTS and chemically modified WTS with sulphuric and hydrochloric acids (reactive sludges—RSs) as coagulants was evaluated. The evaluated WTS contains a higher fraction of inorganic solids and is mainly an amorphous material. The wet WTS (W-WTS) showed a better performance in enhancing WW clarification (up to 76%), as measured by turbidity in comparison with the dry WTS (D-WTS). All RSs improved this performance considerably (up to 98%), and of these, the sulphuric reactive sludge generated from the W-WTS (SRS-W) showed the lowest costs associated with acid consumption for activation. The best treatments with W-WTS and SRS-W significantly improved the removal of solids (total suspended solids > 90% and volatile suspended solids > 80%), organic matter (total biochemical oxygen demand > 50% and total chemical oxygen demand > 55%), and total phosphorus (>75%) compared to natural sedimentation, with slight differences in favour of SRS-W, especially in the removal of phosphorus species. The reuse of WTSs in primary WW treatment becomes a valuable circular economy proposal in the water sector, which simultaneously valorises waste from the drinking water process and contributes to the fulfilment of Sustainable Development Goal 6 (Clean Water and Sanitation)